Nanosilica from Averrhoa bilimbi juice pre-treated rice husk: preparation and characterization - Dominic, C. D. Midhun; Neenu, K. V.; Begum, P. M. Sabura; Joseph, Rani; Rosa, Derval dos Santos; Duan, Yongxin; Balan, Aiswarya; Ajithkumar, T. G.; Soumya, Mary; Shelke, Ankita; Parameswaranpillai, Jyotishkumar; Badawi, Michael (Journal of Cleaner Production, 2023)
The preparation of nanosilica from rice husk without using any concentrated mineral acids is a novel concept. This work proposes a bioleaching strategy to remove metallic impurities from rice husk for the preparation of nanosilica. Herein, nanosilica (BJRHS) was prepared by calcinating Averrhoa bilimbi juice pre-treated rice husks in a muffle furnace. The chemical and atomic structures of commercial precipitated silica (CS), rice husk ash (RHA), and BJRHS were analyzed using different analytical techniques. The optimal leaching time, calcination temperature, and calcination time were 1 h, 500 degrees C, and 6 h respectively. The particle size of BJRHS was found to be 6-12 nm, which is less than that of RHA and CS. The BET surface area of BJRHS (204 m2/g) was found to be greater than RHA (110.5 m2/g) and CS (172.1 m2/g). Mesoporous nanosilica with excellent surface area and purity was produced sustainably from rice husk which could be recommended to use in the field of catalysis, polymer technology, etc.
Keywords: Averrhoa bilimbi juice; Bioleaching; Nanosilica; rice husk

Colocasia esculenta stems for the isolation of cellulose nanofibers: a chlorine-free method for the biomass conversion - Dominic, C. D. Midhun; Maheswary, S.; Neenu, V. K.; Sajadi, S. Mohammad; Rosa, Derval dos Santos; Begum, P. M. Sabura; Mathew, Mariya; Ajithkumar, T. G.; Parameswaranpillai, Jyotishkumar; George, Tresa Sunitha; Resmi, V. C.; Ilyas, R. A.; et al. (Biomass Conversion and Biorefinery, 2024)
The reuse of waste products is the green key to sustainability. The extraction of cellulose nanofibers from Colocasia esculenta stems is presented in the paper. The study proved that the waste biomass could be effectively re-engineered into highly valued cellulose nanofibers (CNFs). Cellulose nanofibers were extracted via a chemo-mechanical route. The pre-treatments included mild alkali hydrolysis (2% NaOH) and chlorine-free bleaching (peroxide bleaching in an alkaline medium). Cellulose I-beta structure was confirmed using C-13 solid-state nuclear magnetic resonance spectroscopy and X-ray diffraction analysis. The elemental analysis of CNFs detected the elements, carbon and oxygen. The CNFs had a crystallinity and transmittance of 71.72% and 60%, respectively. Microscopic studies verified the elimination of non-cellulosic components and the fibrous nature of CNFs. Moreover, the fiber diameter of CNFs was 20-40 nm. Thermal analysis revealed good thermal stability of 335.8 degrees C (T-50) for nanofibers. Long-term aids are numerous in eco-friendly technology. Developing an eco-design will support zero waste ideals, lowers carbon dioxide emissions, and encourages a circular economy. Owing to the merits of natural fibers, they can be adopted in various sectors including packaging, automobile, aerospace, electronics, biomedical, construction, and furniture.
Keywords: acid hydrolysis; cellulose nanofibers; Colocasia esculenta stems; High crystallinity

Extraction, characterization, and life cycle assessment of nanosilica from millet husk: sustainable alternative with low environmental impact - Dominic, C. D. Midhun; Rosa, Derval dos Santos; Barbosa, Rennan Felix da Silva; Anagha, O. V.; Neenu, K. V.; Begum, P. M. Sabura; Kumar, V. Aswathy; Parameswaranpillai, Jyotishkumar; Siriwong, Chomsri; Ajithkumar, T. G.; Shelke, Ankita; Pasc, Andreea (Journal of Cleaner Production, 2024)
Eco-friendly approaches for silica production are highly researched to respond increasing industrial demand for bio-nanofillers. Herein, nanosilica of 10-20 nm with mesoporosity was obtained through a mild oxalic acid pre-treatment of millet husk, followed by calcination at 700 degrees C for 2 h. Compared with commercial precipitated silica (CS) and millet husk ash (MHA) directly obtained by calcination of the husk, the pre-treated silica (MHS) had higher purity, revealed using EDX spectroscopy. Moreover, FTIR and Si-29 NMR showed a higher condensation degree in MHS with 73% of Q4 siloxane bonds vs 4% in MHA. The release of the metal and organic impurities from the husk also allows to reduce the crystallinity of MHS, and to increase the specific surface area from 82 m(2)/g in MHA to 238 m(2)/g in MHS. The type II N-2 adsorption-desorption isotherms of MHA and MHS indicate aggregates of non-porous silica particles. MHS also demonstrated remarkable thermal resilience. According to the LCA analysis, MHS has a 40% lower impact on global warming, a 38% lower impact on human carcinogenic toxicity, and a 38% lower impact on terrestrial acidification compared to rice husk nanosilica. This research thus addresses sustainability challenges by repurposing millet husks, which are readily available due to continuous millet cultivation, particularly in India. By reducing the ecological impact of husk disposal through burning, this study offers an economically viable technology for high-purity silica production, aligning with global efforts to combat climate change and promote sustainable practices.
Keywords: Life cycle assessment; Millet husk; Nanosilica; Oxalic acid